Stability of small incision lenticule extraction over laser in situ keratomileusis at an altitude of 3874 m - Yanming Huang; Yuancheng Zhao; Xiaofan Chen; Huan zou; Rongdi Yuan (Scientific Reports)
Abstract The purpose of this study was to evaluate the stability of small-incision lenticule extraction (SMILE) and laser in situ keratomileusis (LASIK) when ascending from near sea level to an altitude of 3874 m. The visual acuity (VA), intraocular pressure (IOP), spherical equivalent refraction (SER) and biometric parameters of 20 normal subjects (40 eyes, controls) and 36 subjects who underwent corneal refractive surgery (35 eyes with SMILE and 36 eyes with LASIK) were examined in Chongqing (C, 500 m above sea level) and 7–10 days after a collective travel to Shigatse (S, 3874 m above sea level). SER and corneal thickness (CT) were choosed as main indicators of the stability of corneal refractive surgery at high altitude. The IOP decreased and CT increased from C to S, while VA and SER did not significantly change in the control subjects. The VA and IOP of both the SMILE and LASIK subjects did not significantly change at an altitude of 3874 m. At high altitudes, no significant difference in the SER was found among the SMILE subjects, while a significant myopic shift was found among the LASIK subjects. With an increase in the altitude of 3874 m in S, an obvious increase in CT was observed in subjects who underwent corneal refraction surgery. The increase in CT in the SMILE group was significantly less than the increase in CT in the LASIK group. In addition, the biometric parameters of the SMILE and LASIK subjects showed the same minor changes as those of the control subjects when exposed to high altitude. The VA, IOP and biometric parameters of the subjects who underwent SMILE and LASIK remained stable at an altitude of 3874 m. SMILE shows better stability than LASIK in the refractive state and CT when exposed to high altitude. Trial registration: This study was approved by the Ethics Committee of The Second Affiliated Hospital of Army Medical University (ID: 2022-No.084-1) and adhered to the principles of the Declaration of Helsinki. The study was registered at http://www.chictr.org.cn (Study NO. ChiCTR2200059833) on 12/5/2022.